Neutralized Hegemonic Banter: The Persistence of Sexist and Racist Joking Among Undergraduate Students. Issue 1 (26th April 2020) - Lowe, Maria R.; Byron, Reginald A.; O'Hara, Holly; Cortez, Dakota
Abstract : Using a mixed methods approach, this article explores factors that contribute to undergraduate students' beliefs about the harm caused by racist and sexist jokes. Quantitative results indicate that, net of other demographic control variables, college men are less likely to agree that sexist and racist jokes are harmful. Qualitative findings shed light on this pattern via a process we call neutralized hegemonic banter . By connecting students' perspectives about the perceived harm caused by racist and sexist jokes with their larger campus experiences, we extend the literature and demonstrate the role that hegemonic masculinity plays in normalizing racist and sexist joking.